Presenting The Love of God Through The Javanese Hindu Temple of The Sacred Heart of Jesus in Ganjuran Yogyakarta - Yoachim Agus Tridiatno (P3TK, Sanata Dharma University, 2023)
The paper aims to study inculturation in the practices of pilgrimage to the Sacred Heart of Jesus temple in Ganjuran Yogyakarta by exploring its socio-historical background and the current practices. The temple was built in 1927-1930 by Schmutzer family and designed in the Javanese Hindu architecture. After being neglected for 60 years, in 1990, the temple was reinterpreted and revitalized by Father Gregorius Utomo in line to the spirit of the Sacred Heart of Jesus that aspired the Schmutzer family. Now, many pilgrims from various faith visit the temple everyday for getting spiritual and physical healing. This study is an action research where the researcher directly involves in the object to be studied. He did pilgrimage to the temple regularly while he did interviews with the pilgrims for getting the data. Besides, the data are collected through indirect interviews with questionnaires. It is completed with the library sources. The data then was verified, classified, and analized in a descriptive qualitative approach.